Reunión de trabajo con la Dirección de Planeamiento y Aseguramiento de la Calidad de la UEB - Llivi Ruilova, Danny Vicente (2024)
On January 25 of this year, an important work meeting was held, with the participation of Mgtr. Gray Barragán Aroca; Eng. Cristhopher Espinoza Ruiz, professors of the Disaster Risk Engineering program and Eng. Pablo Guillin; with Dr. Fabian Flores, technician from the Planning and Quality Assurance Department of the UEB.